Do Black Lives Matter to White Christians? - Rosario Rodríguez, Rubén (Cross currents, 2018)
The article presents a legal, social, and personal view into the limitations of the Former U.S. President Barack Obama presidency with respect to substantially advancing racial justice as a core aim of American Democracy. It explores the nation's progressive white Christians to deal openly with realities of racism in the post-Obama America after the election of Donald Trump as President. It also discusses the campaign "Black Lives Matter."